Logistic models explaining the determinants of biking for commute and non-commute trips in Lahore, Pakistan - Masoumi, Houshmand; Asim, Muhammad; Anwer, Izza; Aslam, S. Atif Bilal (TeMA - Journal of Land Use, Mobility and Environment, 2020)
The determinants of biking behaviour are less studied in a wide range of developing countries including South Asia. This study takes Lahore, Pakistan as a case-study city to explore the factors defining commute and non-commute bike trips as well as commuting by bike. These issues were analysed by collecting data from 379 subjects accommodating in three socio-economic statuses (lower, medium, and higher) in Lahore in spring 2018. The data were analysed by applying multinomial logistic regression for investigating biking frequency and binomial logistic regression for examining commuting by bike. The results show that gender, age, education, income, purpose of majority of trips, preferred distance to travel using cycle, preferred time to travel using cycle, and preferred bike trip purpose are significantly correlated with biking frequency. The significant determinants of bicycle commuting included categories of education, the purpose of the majority of trips, using bike in combination with other modes, preferred distance to bike, preferred biking time, and preferred bike trip purpose are associated with bicycle commuting. Commuting by bike is more popular in socio-economically weaker neighbourhoods. The discussion of this study shows that the determinants of biking in the sample in Lahore are different from those that have already been addressed by studies undertaken in high-income countries.